Wheat-soybean relay cropping allows corn cultivation as the third crop of the year in Southern Brazil - Nilva Marileia Alves; Vanderson Vieira Batista; Karine Fuschter Oligini; Paulo Fernando Adami; Douglas Junior Bertoncelli (Semina: Ciências Agrárias)
Relay cropping allows soybean to overlap with wheat for a period, reducing the production risks associated with wheat and enabling earlier sowing and harvesting of soybean. This study aimed to evaluate the technical and economic feasibility of a wheat-soybean relay cropping system and the cultivation of corn as a third crop within the same agricultural year. The experiment was conducted using a randomized block design with a 4 x 3 factorial arrangement, featuring three repetitions during the 2019/2020 and 2020/2021 growing seasons. Four wheat inter-row spacings, with configurations of 17 and 22 cm in single and double rows, resulted in soybean row spacings of 51 and 66 cm. Soybean was sown at the wheat's milk and dough grain stages, and a control was sown after wheat harvest with 45 cm inter-row spacing. The best wheat-soybean relay cropping arrangement was 17D, where wheat produced 2,812 and 2,267 kg ha-1, or 69.41 and 64.82% of the total produced by the control treatment in the first and second evaluated years, respectively. In the first year, soybean in the 51-cm arrangement sown during the second sowing season (09/23/19) produced 6,029.42 kg ha-1, which was 32.5% higher than the first season on 09/13/19 and 11.8% lower than the control on 10/03/19. In the second year, the same treatment sown on September 29 yielded 4,235.00 kg ha-1, which was 12.58% more than the first sowing period on September 14 and 7.4% lower than the control sown on October 23, 2020. Although its yield was 1,239 kg ha-1 less than the control (17S), relay cropping allowed corn sowing to be advanced by 15 days, which resulted in a grain yield increase of 1,956 kg ha-1 compared to corn sown after soybean harvest in the conventional system. The trade-off between wheat yield losses and corn yield gains indicates that wheat-soybean relay cropping has a positive balance and can be used as a management strategy to reduce crop risks and achieve higher grain yields per area. Additionally, wheat-soybean relay cropping provides grain yield gains per area and contributes to the productivity of the system, reducing risks for the three crops and yielding higher economic returns in both studied years.